Instructional poetry and its impact on learning Ahmadi Dictionary, for example - رەئوف, پ.ی.د. لوقمان; Faraidun, Dr. Awara; Jawahar, Asst.Prof.Dr. Srusht (Sulaimani Journal for Humanities, 2024)
Although educational poetry is one of the world classifications of poetry, but in terms of development and role and a new poetic phenomenon and Kurds under the influence of Arabic literature, then Persian literature, all under the influence of foreign culture Ahmadi's poetry dictionary was used as a new and different way of teaching and learning by Sheikh Marfi Nodi and was an important turning point for his time. Teaching poetry has varied according to place and person, in the sense that it has been used by some as a poetic feature, by others as a poetic form, and by others as a special placement. This research has primarily made Ahmadi dictionary the main tool to introduce and present the impact on the learning process, with discussion of educational poetry and characteristics and goals of Ahmadi poetry, in a way the steps taken by Sheikh Marf. Then discuss the impact and agenda of educational poetry, with its reflection and interaction on learning and giving examples of poetry in Ahmadi dictionary.
Keywords: Poetry; instructional poetry; teaching; process; dictionary